Wrodzone i nabyte zwężenie odźwiernika u dzieci - Grzelak-Czachorowska, Katarzyna; Krogulska, Aneta (Pediatria Polska - Polish Journal of Paediatrics, 2017)
Pylorostenosis, usually is caused by a congenital idiopathic hypertrophic pyloric stenosis and occurs in infancy. Later in life secondary causes predominate. Pylorostenoses, both congenital and acquired, impair normal movement of gastric contents from the stomach into the duodenum. This condition is called gastric outlet obstruction (GOO). Clinically it is characterized by persistent nausea and vomiting which result in dehydration, electrolyte imbalances and weight loss. In this manuscript we present the classińcation of GOO, epidemiology, etiology, symptoms, diagnosis and treatment of both congenital and acquired pyloric stenoses.